The Representation of Self and Person Knowledge in the Medial Prefrontal Cortex - Wagner, Dylan D. (2012)
Nearly forty years ago, social psychologists began applying the information processing framework of cognitive psychology to the question of how humans understand and represent knowledge about themselves and others. This approach gave rise to the immensely successful field of social cognition and fundamentally changed the way in which social psychological phenomena are studied. More recently, social scientists of many stripes have turned to the methods of cognitive neuroscience to understand the neural basis of social cognition. A pervasive finding from this research is that social knowledge, be it about one's self or of others, is represented in the medial prefrontal cortex. This review focuses on the social cognitive neuroscience of self and person knowledge in the medial prefrontal cortex. We begin with a brief historical overview of social cognition, followed by a review of recent and influential research on the brain basis of self and person knowledge. In the latter half of this review we discuss the role of familiarity and similarity in person perception and of spontaneous processes in self and other referential cognition. Throughout, we discuss the myriad ways in which the social cognitive neuroscience approach has provided new insights into the nature and structure of self and person knowledge.